Synthesis of novel indole-thiazolidinone hybrid structures as promising scaffold with anticancer potential. (15th November 2021) - Kryshchyshyn-Dylevych, Anna; Radko, Lidia; Finiuk, Nataliya; Garazd, Myroslav; Kashchak, Nataliya; Posyniak, Andrzej; Niemczuk, Krzysztof; Stoika, Rostyslav; Lesyk, Roman
Graphical abstract: Highlights: Novel potent antineoplastic azolidinone-indole hybrid molecules. 5-Fluoro-3-(4-oxo-2-thioxothiazolidin-5-ylidenemethyl)-1 H -indole-2-carboxylic acid methyl ester (3a ) affected cell membranes of HepG2 cells. Cytotoxicity of 3a is related to the induction of apoptosis via caspase 3, PARP1 cleavage, Bax up-regulation and DNA damage. Compound 3a did not affect the transition of G1/S phases in HepG2 cells. Abstract: A series of novel indole-azolidinone hybrids has been synthesized via Knoevenagel reaction of 5-fluoro-3-formyl-1 H -indole-2-carboxylic acid methyl ester and some azolidinones differing in heteroatoms in positions 1, 2 and 4. Their anticancer activity in vitro was screened towards MCF-7 (breast cancer), HCT116 (colon cancer), HepG2 (hepatoma), HeLa (cervical cancer), A549 (lung cancer), WM793 (melanoma) and THP-1 (leukemia) cell lines, and a highly active 5-fluoro-3-(4-oxo-2-thioxothiazolidin-5-ylidenemethyl)-1 H -indole-2-carboxylic acid methyl ester (3a ) was identified and subjected to in-depth investigation of cytotoxicity mechanisms. This compound was found to possess the highest cytotoxic action towards tumor cells comparing with the action of other derivatives (1, 3b, 3c, 3d, 3e ). Compound 3a exhibited toxicity toward MCF-7, HCT116, and A549, HepG2 cancer cells, while the non-malignant cells (human keratinocytes of HaCaT line and murine embryonic fibroblasts of Balb/c 3T3 line) possessed moderate sensitivity to it. The compound 3a induced apoptosis in studied tumor cells via caspase 3-, PARP1-, and Bax-dependent mechanisms; however, it did not affect the G1/S transition in HepG2 cells. The compound 3a impaired nuclear DNA in HepG2, HCT116, and MCF-7 cells without intercalating this biomolecule, but much less DNA damage events were induced by 3a in normal Balb/c 3T3 fibroblasts compared with HepG2 carcinoma cells. Thus, 5-fluoro-3-(4-oxo-2-thioxothiazolidin-5-ylidenemethyl)-1 H -indole-2-carboxylic acid methyl ester 3a was shown to trigger DNA damage and induce apoptosis of human tumor cells and it might be considered as an anticancer agent perspective for in-depth studies.